EFFECTIVENESS OF MUSCLE RELAXATION WITH LOW-DOSE SUGAMMADEX COMBINED WITH NEOSTIGMINE IN PATIENTS UNDERGOING ABDOMINAL SURGERY WITH ENDOTRACHEAL ANESTHESIA AT THE ANESTHESIA AND RESUSCITATION DEPARTMENT, THANH NHAN HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: Residual muscle relaxation (RS) is a common postoperative complication affecting patient safety. This study aims to evaluate the results of reversal of neuromuscular blockade after abdominal surgery using low-dose sugammadex combined with neostigmine at the Anesthesia and Resuscitation Department, Thanh Nhan Hospital. Methods: A descriptive cross-sectional study with longitudinal follow-up of responses in patients undergoing abdominal surgery under endotracheal anesthesia and receiving rheostatectomy with low-dose sugammadex combined with neostigmine at the Anesthesia and Resuscitation Department, Thanh Nhan Hospital from May 2025 to September 2025. Results: The study was conducted on 30 patients who underwent endotracheal anesthesia and muscle relaxation reversal with low-dose sugammadex combined with neostigmine. The proportion of females was almost twice as high as that of males, with an average age of 51.07 ± 9.7 years and an average BMI of 22 ± 1.57 kg/m2. The main surgeries were uterine fibroid and colorectal tumor removal, accounting for 33.3%, with an average duration of 119 ± 35 minutes. The TOF score improved at each time point in the study, with: 46.6% of patients achieving a TOF > 0.7 after 2 minutes, 96.7% achieving a TOF > 70% after 4 minutes, and 100% achieving a TOF > 0.7 after 8 minutes. Similarly, for TOF > 0.9, 66.7% of patients achieved a TOF > 0.9 after 4 minutes, 96.7% achieved a TOF > 0.9 after 6 minutes, and 100% achieved a TOF > 0.9 after 12 minutes. Regarding extubation, 50% of patients in the group had their endotracheal tubes removed after 7 minutes, 86.7% after 9 minutes, and 100% after 16 minutes. Conclusion: The combination of Sugammdex 1 mg/kg with Neostigmine 20 µg/kg and atropine 15 µg/kg showed relatively good muscle relaxant efficacy, with a relatively short time to achieve TOF > 90%.
Keywords: Muscle relaxant, low-dose sugammadex, endotracheal anesthesia.